Recycling of carbon fiber-reinforced thermoplastic composite wastes from the aerospace industry. (April 2017) - Li, Hui; Englund, Karl
Post-industrial trimmings and off-cuts of carbon fiber/polyether ether ketone composite were successfully recycled into new composite products. The original composites were thermally characterized by dynamic thermomechanical analysis, differential scanning calorimetry, and thermogravimetric analysis. Melt-bonding and thermoset adhesives were used to bond the carbon fiber/polyether ether ketone. Performance of the bond was evaluated through double lap-shear tests. The carbon fiber/polyether ether ketone scraps were mechanically refined to a variety of elemental sizes, subsequently subjected to high-temperature hot pressing to form panel composites. The influences of element size and processing temperature were evaluated through mechanical testing.